A new species of Phrynobatrachus (Amphibia: Anura: Phrynobatrachidae) from north-western Guinea, West Africa - Hillers, Annika; Zimkus, Breda; Rödel, Mark-Oliver (Zootaxa, 2008)
A new small Phrynobatrachus species from a gallery forest in north-western Guinea is described. Phrynobatrachus pintoi sp. nov. exhibits a combination of unique morphological characters and a distinctive color pattern, including: compact, oval body, short snout, warty dorsum and eyelid (although no eyelid cornicle is present), three pairs of large symmetric black spots on throat and breast, black spots on belly, more than one black bar on thighs and lower leg, finger and toe tips not expanded, and rudimentary web on foot. Furthermore, analysis of mitochondrial DNA from 16S rRNA reveals that this new species differs from other West African species of the genus by a minimum distance of 7%. Genetically the new species is closest to Phrynobatrachus fraterculus, P. cornutus, and P. gutturosus.